Analisis Strategi Kreatif Iklan @Dreamup_id Untuk Meningkatkan Penjualan Digital - Fachmi Adi Pratama; M.Arkansyah (LPPM Stikosa-AWS, 2023)
In line with the business phenomenon that uses social media as the realm of advertising and marketing. This study aims to find out how creative strategies for Instagram @Dreamup_id social media advertising are to increase sales. Dimensions that must be researched are the design and application of creative strategies for pre-production advertising, advertising production to post-production advertising. The research method used is qualitative Robert K. Yin, with data collection through observation, interviews, and documentation. The speakers in this study were the Owner/Creative Director/Advertiser, Copywriter, Art Director/Graphic Designer who participated in making creative advertising strategies to increase sales.